1988
DOI: 10.1126/science.3257584
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Through the EGF Receptor Transfected in IL-3-Dependent Hematopoietic Cells

Abstract: An expression vector for the epidermal growth factor (EGF) receptor was introduced into the 32D myeloid cell line, which is devoid of EGF receptors and absolutely dependent on interleukin-3 (IL-3) for its proliferation and survival. Expression of the EGF receptor conferred the ability to utilize EGF for transduction of a mitogenic signal. When the transfected cells were propagated in EGF, they exhibited a more mature myeloid phenotype than was observed under conditions of IL-3-directed growth. Moreover, exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(138 citation statements)
references
References 32 publications
6
132
0
Order By: Relevance
“…This idea may be strengthened by other groups' observations. For example, Kulik et al, (1997) and Pierce et al, (1988) also found that EGF prevented apoptosis only in EGF receptor-overexpressing Rat-1 ®broblasts or 32D hematopietic cells. In addition, the numbers of EGF receptor were more than 10 5 per cell in those cells which EGF has been reported as a survival factor (Merlo et al, 1995;Yao and Cooper, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This idea may be strengthened by other groups' observations. For example, Kulik et al, (1997) and Pierce et al, (1988) also found that EGF prevented apoptosis only in EGF receptor-overexpressing Rat-1 ®broblasts or 32D hematopietic cells. In addition, the numbers of EGF receptor were more than 10 5 per cell in those cells which EGF has been reported as a survival factor (Merlo et al, 1995;Yao and Cooper, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here show that cbl-b, but not ccbl, inhibits EGFR induced growth in 32D/EGFR cells ( Figure 5). These cells are absolutely dependent on growth factor (either EGF or IL-3) and rapidly undergo apoptosis in the absence of exogenous growth factor (Greenberger et al, 1983;Ihle et al, 1981Ihle et al, , 1982Pierce et al, 1988;Prystowsky et al, 1982). The inhibition of growth in the cbl-b clones is not associated with any cell cycle arrest but it is associated with a dramatic increase in the fraction of cells undergoing apoptosis (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…32D cells do not normally express any endogenous EGFR (or other members of the EGFR family) and do not grow in EGF (Alimandi et al, 1997). In contrast, 32D cells overexpressing the EGFR (32D/EGFR) can be grown in the presence of either IL-3 or EGF (Pierce et al, 1988). These 32D/EGFR cells, used in our experiments, were maintained in Figure 3 cbl-b and c-cbl associate with Grb2.…”
Section: E Ects Of Cbl-b and C-cbl On Egf Induced Cell Growth Of 32d/mentioning
confidence: 94%
See 1 more Smart Citation
“…In addition Pierce et al [30] have introduced the gene encoding the epidermal growth factor receptor into IL3-dependent cells and established EGF-dependent cell growth. Their work shows that tyrosine kinase activity can substitute for IL3, which suggests that the mechanism of IL3 biological activity involves amplification of tyrosine phosphorylation of a select group of proteins.…”
Section: Discussionmentioning
confidence: 99%